A hybrid fiber optic sensing system for simultaneous strain and temperature measurement and its applications - Rajan, Ginu; Milenko, Karolina; Lesiak, Piotr; Semenova, Yuliya; Boczkowska, Anna; Ramakrishnan, Manjusha; Jędrzejewski, Kazimierz; Domański, Andrzej; Woliński, Tomasz; Farrell, Gerald (Photonics Letters of Poland, 2010)
A hybrid fiber optic sensor by integrating polarimetric fiber sensors and fiber Bragg grating sensors for simultaneous strain and temperature measurement is presented in this paper. Two types of polarimetric fiber sensors are used; a Panda fiber and a polarization maintaining photonic crystal fiber. The polarimetric strain sensors give the average strain and temperature information, while the fiber Bragg grating sensors give localized strain information. Two applications of the proposed configuration are also demonstrated in this paper. In the composite materials three fiber sensors are used while for other engineering applications a temperature insensitive polarimetric fiber sensor can be used together with an FBG sensor to measure strain and temperature simultaneously.